CELL-MEDIATED IMMUNITY IN PATIENTS WITH POSTTRAUMATIC LONG BONE OSTEOMYELITIS IN THE COURSE OF MANAGEMENT WITH THE ILIZAROV METHOD - M. V. Chepeleva; N. M. Klyushin; D. S. Leonchuk; E. I. Kuznetsova (Сибирский научный медицинский журнал, 2019)
Cell-mediated immunity parameters were studied in 26 patients (13 males, 13 females) aged 46 years (range: 39-51 years) with fistular type of chronic posttraumatic osteomyelitis of the humerus during the course of surgical treatment with the Ilizarov monofocal transosseous osteosynthesis. The study time-points were pre-surgery period and the following treatment stages: days 3, 7, 21 after osteosynthesis and day 1 after removal of the device. An obligatory criterion of inclusion was absence of postoperative complications and infection recurrence at least a year after removal of the apparatus. Control group were 30 healthy volunteers in the similar age (15 males, 15 females). Carriers of HCV, HIV, HBsAg and persons with concomitant somatic pathology that could affect the results of immunological study were not included. The study of subpopulation composition of the peripheral blood lymphocytes was carried out using laser flow cytometry. The parameters of cell-mediated immunity in patients with a fistular type of chronic posttraumatic osteomyelitis of the humerus were characterized by mild lymphopenia, increase in the number of cells of early and late activation of T lymphocytes (CD3+CD25+, CD3+HLA-DR+). Physiological response of the immune system to debridement of the purulent foci and transosseous osteosynthesis was normalization of the number of activated T-lymphocytes at the final stage of surgical treatment. In general, the dynamic changes of immunological indices were in favor of persistent arrest of the infection process and were confirmed by clinical observations.